Uslub Al-Istifham At-Tarbawiy Fi Surat Al-Ghasyiyah - Moh Nasrudin; Syarifatun Nadia (Jurnal Alsinatuna, 2016)
Qur'an is revealed in a different language style with the previous books. Everyone must have deep knowledge of rhetoric, especially semantics, to understand it. Qur'an uses rhetoric in many verses to explain some crucial issues related to education, such as teaching method which stated in Al-Ghashiyah. The objective of this research is to find out the kind of Istifham which contained in Al-Ghashiyah, the meaning of a query tool in Al-Ghashiyah, and the correlation between Al-Ghashiyah containing istifham with Islamic education. This research uses qualitative approach, with descriptive and inductive analysis method. The research result shows that there are three adawatul istifham in Al-Ghashiyah, they are: "هل" (in the first verse), "أ" (in the seventeenth paragraph), and "كيف" (in the seventeenth to the twentieth verse). The word “هل in this surah has various meanings such as admiration, adoration, exaggeration, and longing. On the other hand, the word " أ " means command, admiration, and warning, while the meaning of " كيف " is for exaltation. The use of هل at the first verse of Al-Ghashiyah shows the importance of screening and observation before the lesson. Therefore, the Adawatul istifham is repeated in seventeenth verse to twentieth verse in order to answer the question of the first verse which show that it is obligatory for all teachers to guide the learners, monitor and evaluate the learning material that will be learned.